A Highly Sensitive Temperature Sensor Based on Au/Graphene-PVP/n-Si Type Schottky Diodes and the Possible Conduction Mechanisms in the Wide Range Temperatures - Cicek, Osman; Altindal, Semsettin; Azizian-Kalandaragh, Yashar (Institute of Electrical and Electronics Engineers (IEEE), 2020)
We report that the sensitive temperature response and possible Conduction Mechanisms (CMs) of Au/graphene-PVP/ ${n}$ -Si type Schottky diodes (SDs) are investigated using the standard Thermionic Emission (TE) theory at low temperatures (LTs) and high temperatures (HTs). The obtained results indicate that the zero-apparent barrier height ( $\phi _{\textit {Bo}}$ - $\phi _{\textit {ap}}$ ) increases while the ideality factor ( ${n}$ ), series and shunt resistances ( ${R} _{s}$ , ${R} _{\textit {sh}}$ ), rectifying rate (at ±2V) and surface states ( ${N} _{\textit {ss}}$ ) decrease with increasing temperature. The $\phi _{\textit {Bo}}$ , ${n}$ and ${R} _{s}$ values are also extracted from Cheung’s functions and, then compared with those obtained TE theory. The conventional Richardson plot ( $\ell {n}$ ( ${I} _{o}$ /T 2)- q/kT ) displays the deviation from the linearity at low-temperatures ( $T\le140$ K). Besides, the experimental value of Richardson constant ( ${A} ^{\ast }$ ) deduced from the intercept of plot was found to be several orders lower than the theoretical value. The discrepancies and higher values for the parameter of ${n}$ are important evidences for the deviation from TE theory. This is mainly attributed to the spatial inhomogeneities of the barrier height and potential fluctuations at the interface including low/high barrier areas. Hence the CMs across diode preferentially flows through these lower barriers/patches at the regions of LTs. The decrement in the ${N} _{\textit {ss}}$ with the enhancement in the temperature is in relation to the molecular restructuring-reordering under temperature and voltage effects. The SDs fabricated with graphene-PVP interlayer exhibit a higher sensitivity ( ${S}$ ) rather than many silicon/SOI-based structures. Numerically, the ${S}$ values are found to be in a range of 1.3 mV/K (LTs)/−1.93mV/K (HTs) in case of ${I} =0.1\,\,\mu \text{A}$ as against much greater values of −8.2 mV/K (LTs)/−7.9mV/K (HTs) for ${I} = 10\,\,\mu \text{A}$ .